The Effectiveness of Economic Tokens to Increase Attention in Children with ADHD - Erdyanto, Easter Fransiska; Andriani, Fitri (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Children with Attention Deficit Hyperactivity Disorder (ADHD) have problems at school, and this can continue into adulthood. They will have difficulty being accepted at school, and often find it difficult to socialize with other children. Children in Indonesia with ADHD disorders increase every year, as many as 2.4% of elementary school students. ADHD is a disorder characterized by inattention, hyperactivity, and impulsivity. ADHD has three types 1) The inattentive type (ADD/Attention Deficit Disorder) focuses on attention and concentration problems. 2) Hyperactive-impulsive focuses on hyperactive and impulsive symptoms such as making lots of movements, talking a lot, having difficulty staying silent. 3) combination type which has symptoms from the two previous types. The focus of this research is the inattentive type or children with attention disorders, because they will have difficulty focusing on something or will quickly feel bored with work in just a few minutes, daydream easily, quickly panic or become confused, and are slow and not flexible in socializing. One intervention that can be implemented to increase attention is a token economy. The aim of this research is to find out how providing economic tokens can reduce ADHD symptoms in children. The client in this research was a six year old student from TK-B class. The data collection methods used in this research were observation, interviews, the Stanford-Binet Intelligence Scale, and the Indonesian hyperactive children's behavior assessment scale (SPPHI). Baseline results showed that the client's behavior was restless, difficult to focus on tasks, and did not complete tasks. As a result of the token economic intervention, the client can be calmer, focused longer, and complete the work assignments given by the teacher. The results of research using economic tokens in children with ADHD disorders suggest that economic tokens given to clients are able to reduce ADHD symptoms.Anak-anak dengan gangguan Attention Deficit Hiperactivity Disorder (ADHD) memiliki permasalahan di sekolah, dan dapat berlanjut hingga mereka dewasa. Mereka akan megalami kesulitan diterima di sekolah, dan seringkali sulit bersosialisasi dengan anak-anak lainnya. Anak-anak di Indonesia dengan gangguan ADHD meningkat setiap tahunnya, sebanyak 2,4% pada siswa sekolah dasar. ADHD adalah gangguan dengan kurangnya perhatian, hiperaktivitas, dan impulsivitas. ADHD memilki tiga tipe 1) tipe inatetentif (ADD/Attention Deficit Disorder) fokus masalah perhatian dan konsentrasi 2) hiperaktif- implusif fokus pada gejala hiperaktif dan implusif seperti banyak melakukan gerakan, banyak bicara, kesulitan diam. 3) tipe kombinasi yang memiliki gejala dari kedua tipe sebelumnya. Fokus penelitian ini adalah tipe inatetentif atau Anak dengan tipe gangguan atensi, karena mereka akan sulit fokus pada sesuatu atau akan cepat merasakan kebosanan dengan pekerjaan hanya dalam beberapa menit saja, mudah melamun, cepat panik atau bingung, lambat dan tidak luwes dalam bersosialisasi. Salah satu intervensi yang dapat diterapkan untuk meningkatkan atensi adalah token ekonomi. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pemberian token ekonomi dapat mengurangi gejala ADHD pada anak-anak. Klien dalam penelitian ini adalah seorang siswa berusia enam tahun dari kelas TK-B. Metode pengumpulan data yang digunakan dalam penelitian ini adalah metode observasi, wawancara, Stanford-Binet Intelligence Scale, skala penilaian perilaku anak hiperaktif Indonesia (SPPHI). Hasil baseline menunjukan perilaku klien tidak dapat diam, sulit fokus pada pengerjaan tugas, dan tidak selesai dalam mengerjakan tugas. Hasil intervensi token ekonomi klien dapat tenang, fokus lebih lama dan ia mampu dalam menyelesaikan perkerjaan tugas yang diberikan oleh guru. Hasil penelitian dengan menggunakan token ekonomi pada anak dengan gangguan ADHD dapat disimpulkan bahwa token ekonomi yang diberikan kepada klien mampu mengurangi gejala ADHD.